A questão agrária e a luta pela terra no Maranhão: o caso do assentamento São Bartolomeu/Luzilândia em Vitorino Freire e Santa Inês - Silva, Henrique Coelho da (2023)
This research aims at analyzing the territorialization process by the peasant squatters who gave rise to São Bartolomeu/Zulilândia Settlement project in Vitorina Freire and Santa Inês municipalities, in the State of Maranhão. In order to achieve the proposed goal, through bibliographic research, we aim at understanding the scenario of the agrarian problem in the capitalistic national territory, as well as in the State of Maranhão and the microregeon of Pindaré, where the settlement is located, and how this process relates to and culminites in its stablishment. We have conducted field research in which it was possible to engage in a dialogue with workers to better understand their specific reality. The partial results enabled us to perceive that the settlement stablishment happened amidst the struggle for lands and the peasants’ endurance, with the support from social agents, such as the church and the STTR (Rural Workers' Union). 27 years since the Settlement stablishment, the peasants' main struggles consist in staying in the land, facing the factors and agents that currently mischaracterize it, such as the land reconcentration, public policy discontinuity, lack of social workers engagement, poor infrastructure and lack of public service.